Multi-touch human-computer interface A - Han, Feimin. (2011)
Touch interface is one of the most direct and intuitive types of Human Computer Interaction (HCI). In recent years, research on building low-cost multi-touch interface has been conducted by Natural User Interface (NUI) Group Community. Based on the information on NUI Group, this project aims at developing multi-touch systems using infrared technology, as well as exploring and developing relevant software that can be applied on the systems. Two sets of multi-touch surfaces were built using the Laser Light Plane (LLP) configuration. Both sets had stable performance, and achieved high level of sensitivity and precision. The Core Community Vision (CCV) software was properly configured to generate touch information in TUIO format. Three categories of software (Adobe Flash, Android x86, and Windows 7) were successfully implemented. A Flash application was created to combine all the applications for demonstration purpose. In addition, a Photo Sharing application was developed in Flash to facilitate inter-device communication.